More than Cramps in Scrubs: Exploring Dysmenorrhea among Women Healthcare Workers - Yáñez-Sarmiento A; Kiel L; Kaufman R; Abioye O; Florez N (Dove Medical Press, 2024)
Anamaría Yáñez-Sarmiento,1 Lauren Kiel,2 Rebekah Kaufman,2 Oyepeju Abioye,2 Narjust Florez2,3 1Department of Oncology, Universidad Icesi, Perímetro Urbano Santiago de Cali, Valle del Cauca, Colombia; 2Department of Thoracic Oncology, Dana-Farber Cancer Institute, Boston, MA, USA; 3Department of Medicine, Harvard Medical School, Boston, MA, USACorrespondence: Narjust Florez, Tel +1 (617) 632-6049, Fax +1 (617) 632-6190, Email Narjust_Florez@DFCI.Harvard.eduAbstract: Though understudied, dysmenorrhea, a painful cramping sensation occurring near and during menses, is the most prevalent gynecological disorder among women of reproductive age, affecting 50- 90% of the global population. Contributing factors of this disorder include poor medical assessment, lack of consciousness, gender bias, moderate to high levels of stress, and depression and anxiety. Among school students and healthcare trainees, dysmenorrhea contributes to short-term absenteeism, lower productivity, creativity, and job performance. Among medical trainees, dysmenorrhea has been found to impact daily activities to a disabling degree in nearly one third of instances, resulting in difficulties in relationships and even self-isolation. Dysmenorrhea further produces substantial global economic losses and higher healthcare costs. To begin to alleviate the extensive issue of dysmenorrhea, we must increase awareness to fully understand its prevalence, risk factors, and potential for effective, affordable, and accessible treatments. Concurrently, our clinical environment must adopt a standard description and assessment tool to prevent, measure, and monitor dysmenorrhea, while on a global scale, we must develop and widely disseminate nationwide labor regulations that address the workforce impact due to the effects of dysmenorrhea.Keywords: women healthcare workforce, impact, gynecological disorder, menstrual pain